2020
DOI: 10.3390/toxics8010014
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics Exposure Causes Negligible Effects on the Oxidative Response Enzymes Glutathione Reductase and Peroxidase in the Oligochaete Tubifex tubifex

Abstract: Microplastics (MPs) are emerging pollutants, which are considered ubiquitous in aquatic ecosystems. The effects of MPs on aquatic biota are still poorly understood, and consequently, there is a need to understand the impacts that MPs may pose to organisms. In the present study, Tubifex tubifex, a freshwater oligochaete commonly used as a bioindicator of the aquatic environment, was exposed to fluorescent polyethylene microspheres (up to 10 µm in size) to test whether the oxidative stress status was affected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…These results further demonstrate that key bioturbating species interact distinctly with plastic contaminated sediments. Among these species, tubificid worms could prove to be important biomonitors of plastic pollution in benthic habitats; they can accumulate higher loads while suffering negligible effects from polyethylene particle exposure (Redondo-Hasselerharm et al 2018;Scopetani et al 2020).…”
Section: Nutrient Cyclingmentioning
confidence: 99%
“…These results further demonstrate that key bioturbating species interact distinctly with plastic contaminated sediments. Among these species, tubificid worms could prove to be important biomonitors of plastic pollution in benthic habitats; they can accumulate higher loads while suffering negligible effects from polyethylene particle exposure (Redondo-Hasselerharm et al 2018;Scopetani et al 2020).…”
Section: Nutrient Cyclingmentioning
confidence: 99%
“…Microplastics can accumulate in aquatic organisms, endangering organisms through physical damage, carrier effects (plasticizer release, enrichment effect with other pollutants), bioaccumulation, and food chain transmission [ 21 , 22 , 23 ]. MPs might induce toxic effects at the individual level (grazing, reproduction, survival, growth) [ 24 ], tissue level (inflammatory response, oxidative damage, fatty vacuoles), cellular level (hepatocyte necrosis) [ 25 ], and genetic level (variety of endocrine disrupting gene expression) [ 26 , 27 ]. However, only a few reports about the toxic effects of microplastics on fish are present, including Danio rerio , Oryzias latipes , and Dicentrarchus labrax [ 25 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Setälä et al ( 2014 ) reported that MP could enter the food chain via ingestion and transferred from one trophic level to the next. Various severely toxic effects have been attributed to MP exposure as well as their leachates in different organisms tested (Pflugmacher et al 2020a , 2021a , b ), but not all (Scopetani et al 2020a ). The presence of MPs also has been reported to disrupt the residence of natural biota and thus could potentially influence biodiversity (Pflugmacher et al 2020b ).…”
Section: Introductionmentioning
confidence: 99%